ANALISIS ALTERNATIF PERENCANAAN DIMENSI TEROWONGAN PENGELAK BENDUNGAN SIDAN - A. A. Ngr. Billy Narendra; Cok Agung Yujana; I Ketut Yasa Bagiarta; Putu Aryastana (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
The deficit of water supply in Bali Province has led to plans to build the Sidan Dam. The dam is designed with an upright core and is equipped with a diversion tunnel that serves to divert the flow of the river during the construction of the dam and control excess water. The diversion tunnel at Sidan Dam was originally designed with a horseshoe shape. The objective of this study is to design the alternative dimensions of the Sidan Dam diversion tunnel with a circular cross-section. The results of the analysis found that the diameter of the diversion tunnel was 5 m, with a 25-year return design discharge of 265.54 m3/sec. The thickness of the tunnel walls is designed to be 0.5 m thick with materials made of reinforced concrete, where the main reinforcement used 3D25-500 and the divider reinforcement used D25-500.